Faktor Perubahan Mata Pencahariaan Masyarakat dari Petani menjadi Pengrajin Batu Bata di Korong Kampung Ladang Nagari Kurai Taji Kecamatan Nan Sabaris Kabupaten Padang Pariaman - sapriyelni yel sapriyelni; ahyuni .; fitriana Syahar (JURUSAN GEOGRAFI FIS UNP, 2018)
ABSTRACT The purpose of the study was to describe the physical and non-pchysical switching factors of the society switching jobs from farmers to be brick craftsmen. The methods used in this study were suvery and questionnaire. The data used in this study were primary and secondary data. The primary data in the study were the result of interviewing the society and the secondary data were the numbers of brick craftsmen in korong kampung ladang nagari kurai taji.This type of research is decriptive quantitative.The method used in this research is survey and questionnaire. While the data used in this study are secondary data and primary data. Primary data in this study interview to the public and secondary data is the number of brick craftsmen in Korong Kampung Ladang Nagari Kurai Taji. The population of this study was all brick craftsmen in Korong Kampung Ladang Nagari Kurai Taji, Nan Sabaris Districks Padang Pariaman, regency and the sampling was done by using slovin formula. With a total sample 72 families of brick craftsmen.The result of this study showed that the factors causing the society’s job switching from farmers to be brick craftsmen are physical and non-physical factors. Physical factors were observed from the condition of the soil, condition of the slope, the use of the field and water, kind of clay found in this area that is secondary clay. Based on the characteristics, secondary clay is formed as a result of weathering rocks in the flat area. Non-physical factors were observed from the work, the income, and the request in which the society prefer to be a brick craftsman because of the high income while the brick request of the consumen was also high. Keyword : Livelihood, Physical factors, Non-physical factors